On exact values of quasiwidths for some classes of differentiable periodic functions of two variables - Akobirshoev, M. O.; Shabozov, M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We determine the exact values of Kolmogorov and linear quasiwidths for some classes of differentiable periodic functions of two variables in the Hilbert space L_2(Q).